The effects of maleic anhydride grafted PP (MAPP) on the mechanical properties of injection moulded kenaf/CNTs/PP composites - Zakaria Razak,; Abu Bakar Sulong,; Norhamidi Muhamad,; Che Hassan Che Haron,; Mohd Khairol Fadzly Md Radzi,; Dulina Tholibon,; Izdihar Tharazi,; Nur Farhani Ismail, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Composite materials have increasingly become crucial in manufacturing engineering products and producing commodity materials in the major industries including; automotive, aerospace, marine, construction, agriculture and health science. However, several improvements regarding the strength, dimensional stability and the cost of production are required. In this study, composite of Kenaf, multi-wall carbon nanotube (MWCNT) and polypropylene (PP) with maleic anhydride-grafted polypropylene (MAPP) are examined. The results highlight that increasing MAPP loading, in turn, increases the value of the mechanical properties. The composites are produced by blending kenaf/MWCNT/PP using a Sigma blade mixer and injection moulding. Injection moulding is a significant operation used to produce plastic products. In the study, Kenaf core fibre was mixed with MWCNT and polypropylene, in addition to MAPP. The MAPP is added by applying different percentage (1, 2, 3 and 4 wt. %) during the blending process. The main objective of the study was to analyse the effects of MAPP concentrations on the mechanical properties of the Kenaf/MWCNT/PP composite. The results of the study established that MAPP 3 wt. % concentration with MWCNT 3 wt. % loading and Kenaf 30 wt. % filler provide optimum results for the composites. There was approximately, a 21% enhance in tensile strength of Kenaf 30 wt. %/MWCNT, 3 wt. %/MAPP, 3 wt. %/PP observed compared to the (without) MAPP composite. The composites with coupling agent stimulate better filler dispersion between Kenaf, MWCNT and PP observed using a scanning electron microscope (SEM) and field-emission scanning electron microscope (FESEM).